2012
DOI: 10.1088/0004-637x/757/1/51
|View full text |Cite
|
Sign up to set email alerts
|

First-2mass Red Quasars: Transitional Objects Emerging From the Dust

Abstract: We present a sample of 120 dust-reddened quasars identified by matching radio sources detected at 1.4 GHz in the FIRST survey with the near-infrared 2MASS catalog and color-selecting red sources. Optical and/or near-infrared spectroscopy provide broad wavelength sampling of their spectral energy distributions that we use to determine their reddening, characterized by E(B − V ). We demonstrate that the reddening in these quasars is best-described by SMC-like dust. This sample spans a wide range in redshift and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
234
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(262 citation statements)
references
References 143 publications
(162 reference statements)
25
234
3
Order By: Relevance
“…Extensive works in the past years uniquely contributed to our understanding of the winds physics, in terms of spatial location, ionization level and energetics involved (see, e.g., Moe et al 2009;Borguet et al 2013 andArav et al 2013). Recent works also suggest that ∼40% of IR selected and SDSS QSOs are BAL QSOs, pointing towards the fact that they are quite common (Dai et al 2008;Allen et al 2011) and that the outflow and unobscured phases may be of comparable length, in agreement with the Hopkins scenario (see also Glikman et al 2012). Moreover, from the analysis of [OIII] luminosity matched obscured and unobscured samples of QSOs at z∼ 0.5 presented in Liu et al (2013) and Liu et al (2014), it has been proposed that high luminosities (L[OIII]> 10 43 erg s −1 ) are characteristic of the peak of quasar feedback phase.…”
Section: Introductionmentioning
confidence: 64%
“…Extensive works in the past years uniquely contributed to our understanding of the winds physics, in terms of spatial location, ionization level and energetics involved (see, e.g., Moe et al 2009;Borguet et al 2013 andArav et al 2013). Recent works also suggest that ∼40% of IR selected and SDSS QSOs are BAL QSOs, pointing towards the fact that they are quite common (Dai et al 2008;Allen et al 2011) and that the outflow and unobscured phases may be of comparable length, in agreement with the Hopkins scenario (see also Glikman et al 2012). Moreover, from the analysis of [OIII] luminosity matched obscured and unobscured samples of QSOs at z∼ 0.5 presented in Liu et al (2013) and Liu et al (2014), it has been proposed that high luminosities (L[OIII]> 10 43 erg s −1 ) are characteristic of the peak of quasar feedback phase.…”
Section: Introductionmentioning
confidence: 64%
“…We focused on observed quantities to explore the parameter space in which different classes of objects live. R W1 -is well correlated with R−K, an oft-used reddened AGN selection criterion (e.g., Brusa et al 2005;Glikman et al 2007Glikman et al , 2012Glikman et al , 2013Georgakakis et al 2009;Banerji et al 2012Banerji et al , 2015, and is thus helpful in such searches where K-band coverage deeper than 2MASS is lacking. Though R W1 -identifies AGNs similar to those selected based on R−K and R 3.6 m [ ] m -colors, the full-sky coverage of WISE, 35% sky coverage of SDSS, and 50% sky coverage of Pan-STARRsmake R W1 -a particularly suitable diagnostic to identify interesting AGN candidates for spectroscopic follow-up over a much larger area of the sky.…”
Section: Discussionmentioning
confidence: 99%
“…These broad lines are generally seen at longer wavelengths (i.e., Hα and possibly Hβ), which sufferless from dust extinction and host-galaxy dilution, and may be reddened Type 1.8 and 1.9 AGNs, 21 rather than pure Type 1 AGNs, since higher-ionization lines such as Mg II are narrow or absent (e.g., Brusa et al 2015). These reddened AGNs are an interesting class of objects, and at least some appear to be in a transition stage between an obscured and unobscured phase within the merger-induced galaxy/black hole co-evolution paradigm (Sanders et al 1988;Hopkins et al 2005;Brusa et al 2010;Banerji et al 2012;Farrah et al 2012;Glikman et al 2012). Indeed, the Hubble Space Telescope followedup a handful of these objects and revealed that they live in trainwreck host galaxies, indicative of merger activity (Urrutia et al 2008;Glikman et al 2015).…”
Section: Selecting Reddened Broad-lined Agnsmentioning
confidence: 99%
See 2 more Smart Citations